2013
DOI: 10.1523/jneurosci.0119-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Ahi1 Affects Early Development by Impairing BM88/Cend1-Mediated Neuronal Differentiation

Abstract: Mutations in the Abelson helper integration site-1 (AHI1) gene result in N-terminal Ahi1 fragments and cause Joubert syndrome, an autosomal recessive brain malformation disorder associated with delayed development. How AHI1mutations lead to delayed development remains unclear. Here we report that full-length, but not N-terminal, Ahi1 binds Hap1, a huntingtin-associated protein that is essential for the postnatal survival of mice, and that this binding is regulated during neuronal differentiation by nerve growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…Cultured cells or brain tissues were homogenized in NP-40,1 × PBS or RIPA buffer with 1× protease inhibitor as previously described [ 57 ]. For immunoprecipitation, the lysates were centrifuged at 800 × g for 5 min, and supernatants were incubated with antibody and Protein A beads (Sigma-Aldrich) at 4 °C overnight, followed by washing with lysis buffer 4 times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured cells or brain tissues were homogenized in NP-40,1 × PBS or RIPA buffer with 1× protease inhibitor as previously described [ 57 ]. For immunoprecipitation, the lysates were centrifuged at 800 × g for 5 min, and supernatants were incubated with antibody and Protein A beads (Sigma-Aldrich) at 4 °C overnight, followed by washing with lysis buffer 4 times.…”
Section: Methodsmentioning
confidence: 99%
“…Culture of primary neurons from mouse brain cortex was performed as described previously [ 57 ]. Briefly, cortical neurons were isolated from the cortex of postnatal day 1 mice.…”
Section: Methodsmentioning
confidence: 99%
“…Second, Heller and colleagues concluded in their study that the SH3 domain is not essential for AHI1 function based primarily on the finding that two homozygous truncating mutations, Arg1066* and Trp1088Leufs*16, are nonpenetrant in a zebrafish model. This conclusion is slightly overstated because (i) previous studies have reported a functional role of the SH3 domain, 14,15 and the frameshift Trp1088Leufs*16 mutation in the SH3 domain was identified in patients with Joubert syndrome; 8 (ii) the evidence from zebrafish is limited in Heller and colleagues' study 13 because the total number of fish examined is not given, creating a lack of statistical data, and the eyeball size seems to be decreased by e23i23MO injection; and (iii) previous studies have demonstrated that different mutations in the same gene may lead to drastically different retinal phenotypes in mice. 16 We believe that Heller and colleagues' viewpoint is extremely meaningful in this field; however, the exact role of the AHI1 protein domains in a mouse model remains unclear and warrants further investigation.…”
Section: Response To Heller and Bolzmentioning
confidence: 95%
“…AHI1 mutation is also associated with a broad range of neurological disorders including schizophrenia [107] and autism [108]. Recent mouse model studies have revealed that Ahi1 is highly expressed in the postnatal brain and interacts with other proteins crucial for neuronal differentiation [109,110]. Table 3 lists the WDR proteins involved in endocrine disorders, many of which are often presented as a part of a ciliopathy.…”
Section: Wdr Proteins Associated With Ciliopathiesmentioning
confidence: 99%